THE DEVELOPMENT STRATEGY OF EDUCATIONAL TOURISM AT RUMAH ATSIRI INDONESIA IN THE ERA OF ADAPTING TO A NEW NORMAL - Suwarni Suwarni; Ute Lies Siti Khadijah; Heryadi Rachmat (Universitas Padjadjaran, 2021)
Rumah Atsiri Indonesia is located in Plumbon Village, Tawangmangu District, Karanganyar Regency, Central Java Province. This study aims to determine the potential and the development strategy of educational tourism at Rumah Atsiri Indonesia in the era of adapting to a new normal. This study used qualitative research method. The data collection technique was done by triangulation, namely a combination of observation, interview, and documentation from various accurate data sources. The data analysis technique used was SWOT analysis. The results of this study indicate that Rumah Atsiri Indonesia with the concept of educational tourism has natural and cultural potentials. The implementation of the CHSE Health Protocols at Rumah Atsiri Indonesia in the era of adapting to a new normal has run smoothly and has received the CHSE Certification label from the Ministry of Tourism and Creative Economy of the Republic of Indonesia. The development strategies of educational tourism at Rumah Atsiri Indonesia are as follows: (a) maximizing the various types of tourist attractions; (b) conducting digital tourism promotion of educational tourism at Rumah Atsiri Indonesia; (c) increasing the quality and quantity of facilities for the visitors; (d) Scheduling annual tourism activities; (e) adjusting the price of products and services with the service quality; (f) increasing the competence of tourism human resources; (g) introducing the various types of plants and their benefits for health; and (h) collaborating with various stakeholders from academia, business, government, community, and media.